Analisis Manajemen Keuangan Pendidikan di Sekolah Menengah Pertama Negeri 13 Kota Jambi - Ratu Rich Shine Manalu RH; Rts.Putri Kiranti; Gabriella Winarny; Ajeng Rahma Destiana; Alga Kristin Sihaloho; Pirgo Simbolon (Jurnal Ilmiah Dikdaya, 2023)
This study aims to provide insights related to educational financial management to readers, observers, academics, and educational practitioners to understand how educational financial management is analyzed from various perspectives related to junior high schools. This research was conducted at SMP Negeri 13 Jambi City Jl. H. Tomok, Tahtul Yaman, Pelayangan District, Jambi City, Jambi. The time this research was conducted was May 23, 2022. This research is a qualitative descriptive research, namely the research method used to examine the natural conditions of objects. Data collection techniques are triangulation (combined), data analysis is inductive/qualitative in nature, and the results of qualitative research emphasize meaning rather than generalization. The approach uses a qualitative approach, namely an approach that describes the data descriptively. The results of this study are that they already have funding sources from the central and regional governments. Expenditure posts have been directed according to the needs required by the school and always report to the relevant department every quarter. All forms of responsible reporting are transparent and accurate, as evidenced by various receipts that support each transaction made. With educational assistance from the government, it can lighten the burden on students in the pursuit of compulsory education, so with this assistance, activities in schools can run smoothly, effectively and efficiently